Unintended Consequences of MRSA Infection: Empiric Non-MRSA Antibiotic Use and Resultant Clostridioides difficile Infection. (October 2020) - Weiland, Anastasiia S.; Lu, Julia Y.; Chen, Caleb S.; Tjoa, Thomas; Singh, Raveena D.; McKinnell, James A.; Center, UCLA Medical; Miller, Loren; Huang, Susan
Abstract : Background: Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for the largest number of invasive infections due to a multidrug-resistant pathogen. Approximately 10% of hospitalized carriers will experience invasive MRSA disease in the year following discharge incurring antibiotic therapy beyond focused treatment of MRSA. Objective: We aimed to quantify the extent of non-MRSA empiric antibiotics incurred by MRSA infections and further assess the risk of Clostridioides difficile Infection (CDI) as a result of treatment of MRSA infection. Methods: The CLEAR Trial was a postdischarge randomized controlled trial of 2, 121 MRSA carriers comparing MRSA education alone to education plus repeated decolonization that demonstrated a 30% reduction in MRSA infection and a 17% reduction in all-cause infection attributable to decolonization in the year following hospital discharge (Huang SS, NEJM 2019). We included all hospitalization outcomes due to MRSA infection in the CLEAR Trial with detailed medication administration records to quantify unintended consequences of MRSA infection related to empiric non-MRSA antibiotic use and resultant CDI. Full-text medical records were reviewed with a standardized abstraction form to collect inpatient administered antibiotics and hospital-associated CDI. Results: In total, 154 hospitalizations due to MRSA infection with a mean length-of-stay of 10.6 days were identified. During 25 hospitalizations (16.2%), patients received only anti-MRSA antibiotics. During the remaining 129 (83.8%) hospitalizations, patients received a mean of 1.6 distinct non-MRSA antibiotics totaling a mean of 6.6 days of therapy (DOT). Empiric non-MRSA therapy was given for 3.2 DOT before MRSA culture results became available and was continued for an additional 3.4 DOT afterward. Among all 849 non-MRSA DOT, the most common were due to piperacillin-tazobactam (293 DOT, 34.5%), levofloxacin (105 DOT, 12.4%), and metronidazole (93 DOT, 11.0%). Across all 154 hospitalizations, a mean of 5.5 non-MRSA DOT was calculated per MRSA hospitalization, with 6 CDI cases (3.9%) as a direct sequelae of empiric non-MRSA antibiotics provided for MRSA infection. Conclusions: Hospitalization for MRSA infection results in extensive non-MRSA empiric antibiotic therapy both before and after MRSA culture results are known. This antibiotic use is associated with a 3.9% risk of CDI that exceeds the national risk of acquiring CDI (3.2 per 1, 000 admissions) by 12-fold during any hospital stay (Barrett ML, AHRQ 2018). The CLEAR Trial findings that postdischarge decolonization reduces MRSA infection and hospitalization by 30% suggests that decolonization may also reduce non-MRSA antibiotic use and CDI in this population. Funding: None Disclosures: None